Comparison of the clinical characteristics and outcomes of COVID-19 in children before and after the emergence of Delta variant of concern in Japan. Issue 4 (April 2022) - Shoji, Kensuke; Akiyama, Takayuki; Tsuzuki, Shinya; Matsunaga, Nobuaki; Asai, Yusuke; Suzuki, Setsuko; Iwamoto, Noriko; Funaki, Takanori; Ohmagari, Norio
Abstract: Delta variant of concern (VOC) is the current predominant severe acute respiratory coronavirus type 2 strain causing coronavirus disease 2019 (COVID-19); however, information regarding the impact of the Delta VOC on clinical features and outcomes in pediatric patients with COVID-19 is limited. We conducted a retrospective observational study using the data of patients <18 years of age in COVIREGI-JP, the COVID-19 registry in Japan. The patients were divided into two groups according to the timing of enrollment in the registry (pre-Delta VOC era, October 2020 to May 2021; and Delta VOC era, August to October 2021), and the clinical characteristics and outcomes were compared between the two groups. During the study period, 950 and 349 pediatric patients were registered in the pre-Delta VOC and Delta VOC eras, respectively. The median patient age was younger and the proportion of patients with underlying diseases was higher in the Delta VOC era than that in the pre-Delta VOC era (10.0 vs 7.0 years, P  < 0.001, and 7.4% [n = 70] vs. 12.6% [n = 44], P  = 0.004, respectively). Significantly more patients were admitted to the intensive care unit in the Delta VOC era than in the pre-Delta VOC era (1.4% [ n = 5] vs. 0.1% [n = 1], P  = 0.006), but no patient in either group died or required mechanical ventilation or extracorporeal membrane oxygenation throughout the study period, suggesting that the overall outcomes in children with COVID-19 remained favorable even in the Delta VOC era in Japan.